2022
DOI: 10.1002/hec.4568
|View full text |Cite
|
Sign up to set email alerts
|

Toward mandatory health insurance in low‐income countries? An analysis of claims data in Tanzania

Abstract: Many low‐income countries are in the process of scaling up health insurance with the goal of achieving universal coverage. However, little is known about the usage and financial sustainability of mandatory health insurance. This study analyzes 26 million claims submitted to the Tanzanian National Health Insurance Fund (NHIF), which covers two million public servants for whom public insurance is mandatory, to understand insurance usage patterns, cost drivers, and financial sustainability. We find that in 2016, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…The current Health Sector Strategic Plan (HSSP V, 2021-2026) aims to increase health insurance coverage to 56% of the population (from 32% in 2018; Durizzo et al, 2022) and raise government health spending to 5% of the gross domestic product (GDP) by 2026 (from 3.8% in 2019; WHO, 2022) to achieve Universal Health Coverage. However, despite plans for unified financial protection under the forthcoming Single National Health Insurance (SNHI) (planned for launch in July 2023), the current arrangements remain highly fragmented with separate mechanisms and funds for formal and informal sector workers.…”
Section: Resultsmentioning
confidence: 99%
“…The current Health Sector Strategic Plan (HSSP V, 2021-2026) aims to increase health insurance coverage to 56% of the population (from 32% in 2018; Durizzo et al, 2022) and raise government health spending to 5% of the gross domestic product (GDP) by 2026 (from 3.8% in 2019; WHO, 2022) to achieve Universal Health Coverage. However, despite plans for unified financial protection under the forthcoming Single National Health Insurance (SNHI) (planned for launch in July 2023), the current arrangements remain highly fragmented with separate mechanisms and funds for formal and informal sector workers.…”
Section: Resultsmentioning
confidence: 99%
“…In Tanzania, only 32% of the population had health insurance as of 2018 14. The NHIF is the most comprehensive health insurance programme in Tanzania and covers 7% of the population based on the number of beneficiaries reported in the NHIF Annual Report from 2020/2021 15.…”
Section: Methodsmentioning
confidence: 99%
“…An interesting study [ 33 ] based on data from Tanzania revealed patterns and consequences of expanding the network of mandatory health insurance coverage for low-income countries. According to the results of the analysis, it was established that expanding the coverage network could negatively affect the financial stability of institutions that serve such applicants.…”
Section: Theoretical Backgroundmentioning
confidence: 99%